Experimental and Numerical Research on the Behavior of Steel Columns with Circular Hollow Cross Sections - Florim Grajçevci; Armend Mujaj; Driton Kryeziu; Guxim Rrudhani; Neritan Shkodrani (Civil Engineering Journal, 2024)
A circular, hollow tubular steel column is introduced for experimental and analytical analysis in this study. A series of axial compression tests for the variation of static schemes are reported in this study. All theoretical, numerical, and experimental analyses are based on the European Standards for the steel structure, respectively EN 1993-1-1. The experimental models of steel columns are conducted on actual steel columns with a length of 3000 mm and a circular hollow section of 114.3/2.8 mm. To assess the behavior and stress values of the columns, various schematically supported systems are modeled, starting from the axial-centered columns to the symmetrical eccentric load and asymmetrical loaded columns. 3D modeling of the steel columns using the finite element program SEISMOSOFT is also developed for such elements. The accuracy of the model is compared with the experimental results using numerical analysis by the finite element method. Finally, the numerical comparison of the results provides a recommendation for the engineers regarding the design and construction of such columns. Doi: 10.28991/CEJ-2024-010-05-014 Full Text: PDF